MANAGEMENT OF RISK FACTORS FOR PRE-ECLAMPSIA - Anita, Anita; Aprina, Aprina; Astuti, Titi (Universitas Aisyah Pringsewu, 2023)
Globally, preeclampsia is still a problem, 10% of pregnant women throughout the world experience preeclampsia, and it is the cause of 76,000 maternal deaths and 500,000 infant deaths every year. Lampung Province is a province where the number of maternal deaths is still quite high, the latest IDHS data in 2018 shows The highest MMR was 818 people (87.99/100,000 KH) in Tanggamus Regency with a total of 16 deaths out of 10,000 births. The exact cause of pre-eclampsia is still not known for certain, so preeclampsia is called